Prenatal caffeine exposure induced renal developmental toxicity and transgenerational effect in rat offspring. (July 2022) - Zhao, Xiaoqi; Li, Bin; Xiong, Ying; Xia, Zhiping; Hu, Shuangshuang; Sun, Zhaoxia; Wang, Hui; Ao, Ying
Abstract: Epidemiological studies revealed that prenatal caffeine exposure (PCE) is associated with adverse gestational outcomes and susceptibility to chronic diseases in offspring, yet the effects of PCE on glomerulosclerosis susceptibility in adult female offspring and its intergenerational transmission remain to be further investigated. Here, we found that PCE caused fetal kidney dysplasia and glomerulosclerosis of the female offspring. Besides, the kidney of F1 offspring in PCE group exhibited the "low expressional programming of AT2R" and "GC-IGF1 programming" alteration. Intergenerational genetic studies revealed that the renal defect and GC-IGF1 programming alteration was inherited to F2 adult female offspring derived from the female germ line, but Low expression of AT2R did not extend to the F2 female offspring. Taken together, PCE caused renal dysplasia and adult glomerulosclerosis in the F1 female offspring, which might be mediated by renal AT2R low expressional programming and GC-IGF1 axis alteration. Furthermore, PCE induced transgenerational toxicity on kidney, and GC-IGF1 programming alteration might be the potential molecular mechanism. This study provided experimental evidence for the mechanism study of the intergenerational inheritance of kidney developmental toxicity caused by PCE. Graphical abstract: Image 1 Highlights: PCE caused renal developmental toxicity，which might be mediated by The low expressional programming of AT2R and the GC-IGF1 axis programming. The F2 offspring of PCE showed slightly glomerulosclerosis. The GC-IGF1 axis alteration may be related to the renal dysfunction in the female offspring of F2 generation female germline.